2017
DOI: 10.1097/meg.0000000000000968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of branched-chain amino acid supplements on muscle strength and muscle mass in patients with liver cirrhosis

Abstract: BCAA supplementation improved low muscle strength in patients with chronic liver disease, but did not increase muscle mass during the treatment period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
2
25
1
1
Order By: Relevance
“…Actually, we have reported that branched chain amino acid (BCAA) supplementation significantly improved protein nutrition and, subsequently, prognosis for sarcopenia patients with liver cirrhosis (29). BCAA supplementation is reported to improve low muscle strength in patients with chronic liver disease (30). Sarcopenia and decreased serum BCAA levels were predictors of minimal hepatic encephalopathy, which spoils QOL (31).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, we have reported that branched chain amino acid (BCAA) supplementation significantly improved protein nutrition and, subsequently, prognosis for sarcopenia patients with liver cirrhosis (29). BCAA supplementation is reported to improve low muscle strength in patients with chronic liver disease (30). Sarcopenia and decreased serum BCAA levels were predictors of minimal hepatic encephalopathy, which spoils QOL (31).…”
Section: Discussionmentioning
confidence: 99%
“…Protein-energy malnutrition is a common characteristic in cirrhotic patients [ 29 ]. BCAA supplement served as substrates for protein synthesis, and important regulators of protein synthesis are effective in improving nitrogen balance and finally resulting in better clinical outcomes [ 30 ]. Some clinical trials also have demonstrated the effect of BCAAs in patients with hepatic encephalopathy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several small Japanese studies have assessed whether BCAA supplementation improves or prevents sarcopenia in cirrhotic patients; however, most of these are limited by low patient numbers, confounding, poor long-term follow-up, and lack of appropriate control groups 65,66 . Hiraoka et al prospectively studied 33 patients with cirrhosis who underwent BCAA supplementation as a late evening snack and also walking exercise (additional 2000 steps/day), over a three-month period 65 .…”
Section: Branched-chain Amino Acid Supplementationmentioning
confidence: 99%
“…Uojima et al prospectively studied 82 cirrhotic patients with persistent hypoalbuminemia (albumin <3.5 g/dL) after undergoing standard nutrition therapy for at least 28 days, who then underwent BCAA supplementation for 24 weeks and again acted as their own controls 66 . After completing the study period, participants had improved muscle strength as measured by hand-grip strength test (pre-treatment 22.2 ± 6.3 kg, post-treatment 23.9 ± 6.4 kg, p<0.001); however, there was no difference in skeletal muscle mass index as measured by bioelectrical impedance analysis divided by height squared (pre-treatment 7.40 ± 1.62, post-treatment 7.30 ± 1.49, p = 0.333).…”
Section: Branched-chain Amino Acid Supplementationmentioning
confidence: 99%
See 1 more Smart Citation